The Use of Virtual Reality for Pain and Anxiety Reduction: A Literature Review - Marčiūtė, Gerda; Lapeikis, Ignas; Kasputytė, Greta (Acta medica Lituanica, 2026)
Virtual reality (VR) is being increasingly used as an adjunctive tool to reduce procedural pain and anxiety during various interventional procedures. Forty articles published between 2020 and 2025 were reviewed. The articles reviewed discuss the use of virtual reality to reduce procedural pain and anxiety during various interventional procedures. The results of the literature analysis show that VR can effectively direct patients’ attention and reduce the subjective intensity of pain and fear during procedures across different age groups. VR has been successfully applied to interventional procedures such as vaccination, blood draws, and peripheral vein punctures in children, as well as to a wide range of interventions in obstetrics, orthopaedics, endovascular surgery, cardiology, and dentistry. The studies reviewed confirm that VR is a safe method that rarely causes adverse side effects and can be integrated into clinical practice, contributing to patient comfort, emotional well-being, and the overall satisfaction with the procedure.
Keywords: virtual reality; immersive VR; procedural pain; anxiety; interventions